FOR EN OPLØSNING AF ALLE SELVFØLGELIGHEDER: Et teoretisk bidrag til den kritiske analyse - Nielsen, Morten (Tidsskriftet Antropologi, 2002)
The article suggests new theoretical and methodical ways of carrying out critical anthropology. The objective is an attempt to integrate a historical awareness in anthropological studies of symbol systems that often are perceived as standig outside history, such as love, morality or even the economic system. The point of departure is a fresh reading of Michel Foucault’s later works, where the concept dispositif is being highlighted. Dispositif is a theoretical metaphor for a socially established heterogeneous morality which binds people together by creating dispositions for actions. Michel Foucault’s thoughts are used in analysis of political processes in Northeast Brazil, where participatory processes are changing the position of local community leaders in poor urban neighbourhoods. Through a dispositional analysis of the concept of participation, the article suggests new ways of understanding conventional truisms. Consequently, empirical data are perceived through an altered analytical lense.